Assessment of the environmental impacts associated with hydropower. (April 2017) - Botelho, Anabela; Ferreira, Paula; Lima, Fátima; Pinto, Lígia M. Costa; Sousa, Sara
Abstract: The production of electricity from hydropower results in several environmental impacts that, in only some instances, have been analysed from an economic valuation approach. Moreover, as environmental impacts largely depend on the specific characteristics of the case study, benefit transfer techniques are inadequate for valuation. The present paper demonstrates through the review of valuation studies on the environmental impacts of this technology, and the analysis of the different environmental impacts associated with hydropower for specific case studies that in fact benefit transfer should not be applied as each hydropower plant has specific and different impacts. The paper demonstrates the importance of a case study approach, for defining priorities with respect to alternative hydropower production facilities. Finally, the paper demonstrates that choice experiments are particularly suited for valuing the identified environmental impacts, being relevant for policy planning purposes.